Reproductive age mortality survey: a tool to determine level of underreporting of maternal mortality - Badalia, Sonika; Parashar, Anupam; Dhadwal, D. S.; Sharma, Deepak (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: For achieving sustainable development goals, tracking all maternal deaths without missing any is a crucial step. Underreporting of maternal deaths is an issue especially in developing countries like India. Objectives of this study were to estimate maternal deaths using Reproductive Age Mortality Survey (RAMOS) methodology in a district of North India and to study medical causes responsible for maternal deaths. Methods: A Reproductive Age Mortality Study (RAMOS) was carried out in a district of North India for the period 2009 to 2012. Records of female deaths in the reproductive age group were reviewed using multiple sources and verbal autopsy was conducted. Maternal deaths thus identified were compared with the officially reported maternal deaths for the same period for finding out the under reporting. Verbal autopsy was conducted to find out causes of maternal deaths. Results: A total of 16 women were identified as maternal deaths using RAMOS methodology. The officially reported maternal deaths were 8, thus under reporting of 100%. The 16 maternal deaths consisted of 14 (87.5%) direct maternal deaths and 2 (12.5%) indirect maternal deaths. One or the other form of delay was recognized in 8 of 16 maternal deaths. There was delay in recognizing the warning signs for urgent health care requirement (first delay) in 4 of 16 maternal deaths. There was delay on part of health facility to diagnose the complication and act appropriately (third delay) in 4 cases. Conclusions: It is concluded that the reporting system for maternal deaths need to be strengthened. Health workers should be adequately trained on reporting maternal death cases. On this foundation verbal autopsy should be conducted for all the reported deaths of women of reproductive age group to know the circumstances leading to maternal deaths.